Gambaran Stres Kerja dan Koping Guru SMA saat Pembelajaran Daring selama Pandemi - Rafael Indra; Gracia Christifera Lian; Jovanna Abigail Immanuel Putri; Luisa Valencia; Yoela Elysia Sifra Ully Santoso; Immanuel Yosua (Jurnal Ilmiah Psikologi MIND SET, 2021)
Covid-19 pandemic forced the Government of Indonesia to shut down all the schools at all levels including high school and change it to online learning to respond to this situation. With these transitions along with increased demands that must be managed may cause stress for high school teachers. Moreover, this condition can affect their performance in teaching and may impact educational quality. This study aims to describe work stressors and coping strategies for high school teachers in online learning during the pandemic. In this research, the method used was a qualitative with phenomenological approach. The data are taken from three high school teachers who experienced a transition from face-to-face to online teaching in South Tangerang with interview technique. The results show that during this pandemic, teachers are experiencing various stressors including financial decline, adjustment to policies and technology, increased workload, and multiple role conflicts. Several coping strategies are used to deal with their stress such as emotion-focused (escapism, self-blame, and seeking meaning) and problem-focused coping strategies (instrumental action, caution, and negotiation). The results indicate that it is necessary to pay attention to teacher’s mental health conditions during the pandemic and provide support needed to help them dealing with their work stressor.